Aprendizagem baseada em problemas (ABP) como estratégia pedagógica na construção e uso das expressões algébricas por meio da linguagem Python no ensino superior - Bossi, Kátia Milani Lara (2020)
The university professor in the initial mathematics disciplines needs to reconstruct several concepts that started in elementary and high school. Higher Education institutions need to reduce these learning deficiencies through different mechanisms, since the current society has demanded critical individuals capable of carrying out collaborative practices and being able to find answers relevant to different situations, thus requiring a more dynamic teaching in which students are the subject of their learning process. The objective of this study is to investigate and apply Problem Based Learning (PBL) as a pedagogical strategy in the construction and use of algebraic expressions, through the Python programming language, with a case study applied to a Technology in Systems Analysis and Development in Higher Education. An exploratory research was carried out with quantitative and qualitative data and the subjects of the research were students of the Technology Analysis and Systems Development course, enrolled in the discipline of Applied Mathematics in 2020. An activity was applied using PBL methodology in which it contained eight stages carried out in two meetings. And, as a product, the students built a small software encoded in the Python language as a solution to the problems listed by them in the second stage of the activity. Data collection was performed using two questionnaires. During the activity the students had the opportunity to use analysis and evaluation skills. The activity was well accepted and, the presence of a programming language in a math activity, also generated positive reactions. Even in the face of the difficulties found in a Pandemic in which it was necessary to change the format of the face-to-face classes for Emergency Remote Teaching, it was possible to carry out the Research using the technological means available.